2008
DOI: 10.3148/69.2.2008.91
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Screening And Nutritional Intervention Among Older Adults in Healthcare Facilities

Abstract: A nutritional screening and early intervention program was administered to older adults in a subacute care facility. The study group was recruited among patients aged 65 or older, who were admitted to the geriatric and rehabilitation units of two hospitals. Two simple, reliable, and valid tools were used to screen subjects for the risk or presence of malnutrition. Those determined to be at high nutritional risk (n=62) were included in the study. Dietitians then conducted a full nutritional assessment and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
14
0
7
Order By: Relevance
“…This guideline places nutrition assessment and screening in the context of intervention as part of nutrition care 23 , 48 . ‐ 51 Nutrition intervention in malnourished patients was associated with improved nutrition status, 48 , 49 nutrient intake, 50 physical function, 49 , 51 and quality of life 51 . In addition, hospital readmissions were reduced (Table 7).…”
Section: Practice Guidelines and Rationalesmentioning
confidence: 99%
“…This guideline places nutrition assessment and screening in the context of intervention as part of nutrition care 23 , 48 . ‐ 51 Nutrition intervention in malnourished patients was associated with improved nutrition status, 48 , 49 nutrient intake, 50 physical function, 49 , 51 and quality of life 51 . In addition, hospital readmissions were reduced (Table 7).…”
Section: Practice Guidelines and Rationalesmentioning
confidence: 99%
“…[22][23][24][25][26][27] The results indicated that positive health outcomes are seen when older populations are treated by dietitians in the community. Table 2 shows the studies' characteristics and outcome measures with statistically significant results.…”
Section: Studies Of Malnutrition In Older Populationsmentioning
confidence: 76%
“…[23][24][25][26][27] One study also showed that dietetic training of other health professionals in nutrition improved their nutrition knowledge long-term and their reported management of malnutrition. 22 The economic analyses also demonstrated the financial benefit of dietetic intervention in primary care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations